Unveiling the hidden risk: paternal smoking and alcohol exposure prior to conception as independent factors for allergic rhinitis in children - Chen, Junrong; Liu, Xiaohua; Su, Wenwen; Liu, Zixin; Sun, Guoying; Yang, Yide; Tian, Mei; Li, Jian; Dong, Yunpeng (Frontiers in Pediatrics, 2024)
Introduction:Limited knowledge exists regarding the impact of paternal smoking and alcohol exposure on the development of allergic rhinitis in offspring. Our study aimed to investigate the potential association between preconception paternal smoking and alcohol exposure and the likelihood of children allergic rhinitis.:A retrospective case-control study of 556 prepubertal children aged 3-12 years was performed. The participants were 278 children with allergic rhinitis and 278 healthy controls matched for age and gender. Self-administered questionnaires were distributed and collected on-site, focusing on various factors related to the children's fathers, mothers, and the children themselves during the first year of life and the past 12 months, from March to October 2022.Results:Multivariate analysis demonstrated that paternal smoking, paternal alcohol consumption prior to conception, paternal allergic diseases, children with a family history of allergies, maternal allergic diseases and pregnancy complications were identified as independent risk factors for allergic rhinitis in their offspring. Moreover, after considering confounding factors, it was observed that paternal smoking exceeding 5 cigarettes per day in the year preceding pregnancy and exceeding 11 years significantly elevated the likelihood of allergic rhinitis in children (OR=2.009 and 2.479, respectively). Furthermore, the consumption of alcohol by the father at intervals of less than one month in the year prior to pregnancy and a duration of alcohol consumption exceeding 11 years prior to pregnancy are both associated with a significantly increased risk of allergic rhinitis in children (OR=2. 005 and 3.149, respectively).Conclusions:Paternal smoking and alcohol consumption prior to conception contribute to an increased risk of allergic rhinitis in children, with the risk being dependent on the dosage and duration of exposure. Therefore, it is important to not only focus on personal and maternal environmental exposures when considering the occurrence risk of allergic rhinitis in children, but also to consider paternal detrimental exposures prior to conception.